2011
DOI: 10.1089/vbz.2009.0244
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Public Park Accessibility to Dogs to the Presence of Toxocara Species Ova in the Soil

Abstract: This survey was conducted to determine prevalence of Toxocara spp. ova in public parks in Erzurum, Turkey. A total of 214 soil samples were collected from July 2007 to June 2008 in 36 public parks, of which 28 were unfenced and 8 were fenced. Prevalence of Toxocara spp. was 64.28% in unfenced public parks, while no contamination was observed fenced public parks (p<0.001). Average number of Toxocara spp. ova was 1.43 per 50 g sand ranging from 1 to 7. Moreover, soils from unfenced public parks were contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
1
26
0
2
Order By: Relevance
“…and the number of stray cats and dogs. In addition, we collected the soil specimens from unfenced parks of Ahvaz City, and the stray infected dogs and cats have easy access to these parks, and the higher prevalence of the parasite in the soil of unfenced public parks than fenced parks has been reported [8]. The prevalence rate of human toxocariasis is associated with the degree of soil contamination with the parasite eggs, because the eggs are resistant to environmental conditions [3,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the number of stray cats and dogs. In addition, we collected the soil specimens from unfenced parks of Ahvaz City, and the stray infected dogs and cats have easy access to these parks, and the higher prevalence of the parasite in the soil of unfenced public parks than fenced parks has been reported [8]. The prevalence rate of human toxocariasis is associated with the degree of soil contamination with the parasite eggs, because the eggs are resistant to environmental conditions [3,15].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the localization of the larvae and the response of host immunity, the infection has four clinical types including ocular larva migrans (OLM), neurological toxocariasis (NT), visceral larva migrans (VLM), and covert toxocariasis (CT) [1,6]. The prevalence of Toxocara species egg in public parks in some countries was estimated to be 0.55%, 6.73%, 9.75%, 11.57%, 11.87%, 14.03% and 28.31% in Middle East, Latin America, North America, Asia, Turkey, Australia and Europe, respectively [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…9,40 Furthermore, efforts aimed at wildlife and nuisance animal exclusion (eg, fencing) have resulted in a reduction in environmental contamination with infectious pathogens. 59 The risks of wildlife-derived infections vary on the basis of the prevalence of pathogens circulating in the local wildlife and the degree of wildlife contact afforded by the setting. 40 Although complete exclusion of wildlife is unlikely or unrealistic for most outdoor group settings, efforts should be directed to areas where close contact between dogs and wildlife is most likely to be unmonitored (eg, dog housing).…”
Section: Insect and Wildlife Controlmentioning
confidence: 99%
“…Also in southern Brazil, Cassenote et al (2011) observed that the frequency of geohelminthes in fenced parks (11.1%) was significantly lower than that verified in non-fenced off areas (45.3). Similarly, Avcioglu & Balkaya (2011) observed in Turkey that fenced parks were free of Toxocara eggs, while 64.3% of open areas were contaminated with eggs. Periodic prophylactic deworming of companion animals and educational measures aimed at pet owners are also critical for controlling infections by soil-transmitted helminths (Stull et al, 2007).…”
Section: Prevention and Control Of Zoonotic Soil-transmitted Helminthmentioning
confidence: 66%